Structural bases for N‐glycan processing by mannoside phosphorylase. (1st June 2015) - Ladevèze, Simon; Cioci, Gianluca; Roblin, Pierre; Mourey, Lionel; Tranier, Samuel; Potocki‐Véronèse, Gabrielle
<x xml:space="preserve">Abstract</x> The first crystal structure of Uhgb_MP, a β‐1, 4‐mannopyranosyl‐chitobiose phosphorylase belonging to the GH130 family which is involved in N‐glycan degradation by human gut bacteria, was solved at 1.85 Å resolution in the apo form and in complex with mannose and N‐acetylglucosamine. SAXS and crystal structure analysis revealed a hexameric structure, a specific feature of GH130 enzymes among other glycoside phosphorylases. Mapping of the −1 and +1 subsites in the presence of phosphate confirmed the conserved Asp104 as the general acid/base catalytic residue, which is in agreement with a single‐step reaction mechanism involving Man O3 assistance for proton transfer. Analysis of this structure, the first to be solved for a member of the GH130_2 subfamily, revealed Met67, Phe203 and the Gly121–Pro125 loop as the main determinants of the specificity of Uhgb_MP and its homologues towards the N‐glycan core oligosaccharides and mannan, and the molecular bases of the key role played by GH130 enzymes in the catabolism of dietary fibre and host glycans.